The Influence of Awareness, Moral Obligations, Tax Access, Service Quality and Tax Sanctions on Taxpayer compliance in Paying Motor Vehicle Tax - Linda Nur Yunianti; Negina Kencono Putri; Yudha Aryo Sudibyo; Ascaryan Rafinda (Journal of Accounting and Strategic Finance, 2019)
This research aimed to get empirical evidence about the influence of awareness, moral obligation, access tax, quality of service, and tax penalties on taxpayer compliance in paying motor vehicle tax in Banyumas district. The theory used is the Attribution Theory. The population in this research are all taxpayers' two-wheelers and three-wheelers motor vehicle registered in the office of UPPD Banyumas district until 2017 that as many as 501.400 vehicles. The samples used of 100 respondents was calculated based on the formula Slovin of sampling convenience. The data collected by the survey method through a questionnaire. The data analysis technique used in this research is multiple linear regression. The results showed that awareness, a moral obligation, quality of service, and tax penalties have a positive effect on taxpayer compliance in paying motor vehicle tax. Furthermore, the variable of access taxes is positive effect but statistically not significant on taxpayer compliance in paying motor vehicle tax.